Structural characterization of the NAP; the major adhesion complex of the human pathogen Mycoplasma genitalium. Issue 6 (17th July 2017) - Scheffer, Margot P.; Gonzalez‐Gonzalez, Luis; Seybert, Anja; Ratera, Mercè; Kunz, Michael; Valpuesta, José M.; Fita, Ignacio; Querol, Enrique; Piñol, Jaume; Martín‐Benito, Jaime; Frangakis, Achilleas S.
Summary: Mycoplasma genitalium, the causative agent of non‐gonococcal urethritis and pelvic inflammatory disease in humans, is a small eubacterium that lacks a peptidoglycan cell wall. On the surface of its plasma membrane is the major surface adhesion complex, known as NAP that is essential for adhesion and gliding motility of the organism. Here, we have performed cryo‐electron tomography of intact cells and detergent permeabilized M. genitalium cell aggregates, providing sub‐tomogram averages of free and cell‐attached NAPs respectively, revealing a tetrameric complex with two‐fold rotational (C2) symmetry. Each NAP has two pairs of globular lobes (named α and β lobes), arranged as a dimer of heterodimers with each lobe connected by a stalk to the cell membrane. The β lobes are larger than the α lobes by 20%. Classification of NAPs showed that the complex can tilt with respect to the cell membrane. A protein complex containing exclusively the proteins P140 and P110, was purified from M. genitalium and was structurally characterized by negative‐stain single particle EM reconstruction. The close structural similarity found between intact NAPs and the isolated P140/P110 complexes, shows that dimers of P140/P110 heterodimers are the only components of the extracellular region of intact NAPs in M. genitalium . Abstract : Isosurface representation of an intact Mycoplasma genitalium cell showing the three‐dimensional distribution of the surface adhesion complexes, NAPs (blue), on the surface of the plasma membrane (light grey), with an inset showing the sub‐tomogram average.